Analysis Bachelor of Public Health Needs and Policy Constraints Aspects in the Health Department Konawe District - Syawaluddin, Syawaluddin; Azizi Jayadipraja, Erwin; Kamalia, La Ode (Waluya The International Science of Health Journal, 2022)
Introduction: The initial survey conducted at the Konawe District Health Office shows that the distribution of Public Health Bachelors has not been evenly distributed until now, where there are still health centers in Konawe District which lack public health personnel. In addition, the management of the duties of the Bachelor of Public Health at the Health center is sometimes not in accordance with the main task. So that researchers intend to conduct research on "Analysis of the Needs of Undergraduate Public Health Workers and Constraints on Policy Aspects at the Konawe District Health Office" Method: This study uses two types of research, namely descriptive quantitative and qualitative to analyze the constraints in the distribution bachelor of public health personnel. The sample was sourced from 137 bachelor of public health personnel from the Head of Public Health Center while the Head of Administration and Ordinary Informants were informants in this study spread from 29 Public health center. Result: The need for public health workers in accordance with the Minister of Health Regulation No. 75 of 2014 at least 2 people per Health center and aspects of policies that have not been running optimally are obstacles in the distribution bachelor of public health personnel. Conclusion: Local governments should carry out data-based Health Human Resources (HR) planning so that planning documents are able to accurately project the calculation of needs in accordance with the current health situation.